Multimode Operation of Single Phase Matrix Converter with Safe Commutation Strategy - Boydak, Merve; Orhan, Ahmet; Caliskan, Abuzer (Institute of Electrical and Electronics Engineers Inc., 2020)
In this study, the multimode operation of Single-Phase Matrix Converter (SMPC) is examined. The SPMC was operated as a controlled rectifier and frequency converter using a single driver circuit. Mode selection is provided by changing the value of the constant block in the driver circuit. In the rectifier mode, the sinusoidal input voltage was rectified and transferred to the output. Output voltage at the desired frequency value was generated in the frequency changer mode. Voltage peaks in frequency converter mode were prevented with the safe commutation strategy used. Harmonics in the output voltage were examined for different modulation index values. Switches in the SPMC are switched using Sinusoidal Pulse Width Modulation (SPWM) technique. MATLAB/Simulink was used for simulation. © 2020 IEEE.
2nd International Conference on Electrical, Communication and Computer Engineering, ICECCE 2020 -- 12 June 2020 through 13 June 2020 -- Istanbul -- 162684
Keywords: controlled rectifier; frequency conversion; Single phase matrix converter (SPMC); sinusoidal pulse width modulation (SPWM)